2020
DOI: 10.1109/access.2020.3032108
|View full text |Cite
|
Sign up to set email alerts
|

Uneven Illumination Surface Defects Inspection Based on Saliency Detection and Intrinsic Image Decomposition

Abstract: Surface defect detection based on computer vision remains a challenging task due to the uneven illumination, low contrast and miscellaneous patterns of defects. Current methods usually present undesirable detection accuracy and lack adaptability for the various scenes. In the paper, the novel uneven illumination surface defects inspection (UISDI) method is proposed to address these issues. First, the multi-scale saliency detection (MSSD) method is proposed to construct a coarse defect map and obtain the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The method proposed in this study can be applied to two processes: the process of assembling products in the assembly area when the parts are inputted as shown on the left of Figure 1 , and the process of judging the presence or absence of defects in the inspection area when products are inputted as shown on the right of Figure 1 . This inspection process determines the presence of defects related to the appearance or assembly state and not the function of the product [ 10 , 11 ]. The method proposed in this study performs alignment correction for round-shaped products as well, as shown in Figure 2 .…”
Section: Structure Of the Assembly And Inspection Process Systemmentioning
confidence: 99%
“…The method proposed in this study can be applied to two processes: the process of assembling products in the assembly area when the parts are inputted as shown on the left of Figure 1 , and the process of judging the presence or absence of defects in the inspection area when products are inputted as shown on the right of Figure 1 . This inspection process determines the presence of defects related to the appearance or assembly state and not the function of the product [ 10 , 11 ]. The method proposed in this study performs alignment correction for round-shaped products as well, as shown in Figure 2 .…”
Section: Structure Of the Assembly And Inspection Process Systemmentioning
confidence: 99%
“…) || 1 b + (8) where, ( , ) f w b is the primal objective function and is the penalty factor that increases gradually along with iterations. Till now, we derive the unconstrained optimization objective function, which can facilitate the succeeding optimization algorithm design process.…”
Section: B Efficient Heuristic Alternating Optimization (Hao) Algorithmmentioning
confidence: 99%
“…Ever since the pioneer work of Itti et al [4], there has been an increasing interest in predicting this saliency map with computer algorithms [5]- [7]. Also, the advancement of saliency modeling technique has benefited a wide range of scientific and engineering fields, such as industrial defect detection [8], remote sensing interpretation [9], multi-media applications [10], etc.…”
Section: Introductionmentioning
confidence: 99%
“…So, based on computer vision, surface defect detection remains challenging due to uneven illumination and non-stable image-obtaining conditions [19]. Low contrast and the heterogeneous patterns of defects make this task even more complicated.…”
Section: Introductionmentioning
confidence: 99%